A case of papillary thyroid carcinoma in toxic adenoma: are hyperfunctioning nodules truly innocent all the times? - Yurekli, Banu Sarer; Ozisik, Hatice; Kutbay, Nilufer Ozdemir; Makay, Ozer; Ozgen, Gokhan; Akgun, Aysegul (International Surgery Journal, 2017)
Thyroid nodule is seen commonly in clinical practice. Thyroid scintigraphy should be performed for the evaluation of thyroid nodules in case of suppressed TSH. We would like to present a case of toxic adenoma with the diagnosis of papillary thyroid carcinoma. Forty-four-year-old female patient had applied to the hospital with the diagnosis of thyroid nodule. Thyroid fine needle aspiration biopsy (FNAB) was performed for the evaluation of thyroid nodule measured as 47x12 mm. This nodule was in mixed solid form bearing cystic components. FNAB revealed that the thyroid nodule was benign. Our ultrasonographic evaluation was consistent with a thyroid nodule located at right lobe with a diameter of 43x18x28 mm. The patient underwent right thyroid lobectomy. Pathology report revealed macrofollicular variant of papillary thyroid carcinoma. The tumor was 3.5 cm in diameter with regular margin and 0.2 cm away from the surgical border. The tumor didn’t spread out of the thyroid capsule. Second thyroid surgery was performed due to remaining thyroid tissue. After that ablative radioactive iodine therapy was applied. Guidelines in Endocrine literature report that hyperfunctioning nodules are almost always benign. However, the risk of malignancy was reported as a weighted rate of 3.1%. As follicular lesions are seen in high percentage in hot nodules, surgery should be recommended in case of the cytological results of a follicular neoplasm of a hyperfunctioning nodule. So, hyperfunctioning thyroid nodules warrants careful evaluation and appropriate therapy. We wanted to draw attention of the clinicians for this rare issue.